PENGARUH INTENSITAS PENGGUNAAN E-COMMERCE DAN GAYA HIDUP KONSUMTIF TERHADAP PENGELOLAAN KEUANGAN PRIBADI MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR. - Ivana Melina Pasaribu; Benjamin Albert Simamora; Anggun Tiur Ida Sinaga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of e-commerce usage intensity and consumptive lifestyle on the personal financial management of students of the Economic Education Study Program, FKIP HKBP Nommensen University Pematangsiantar. This research employs a quantitative approach with a causal associative method. The sample consists of 75 respondents selected using a simple random sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS.The results show that: (1) e-commerce usage intensity has a significant effect on personal financial management with a t-value of 3.801 and a significance level of 0.000 < 0.05; (2) consumptive lifestyle has a significant effect on personal financial management with a t-value of 6.289 and a significance level of 0.000 < 0.05; and (3) simultaneously, e-commerce usage intensity and consumptive lifestyle have a significant effect on personal financial management with an F-value of 32.894 and a significance level of 0.000 < 0.05.The coefficient of determination (R²) is 0.477, indicating that 47.7% of the variation in personal financial management can be explained by the independent variables, while the remaining 52.3% is influenced by other factors outside this study.The findings indicate that higher levels of e- commerce usage intensity and consumptive lifestyle tend to lead to less optimal personal financial management among students.